Granzyme B Is an Essential Mediator in CD8(+) T Cell Killing of Theileria parva-Infected Cells - Yang, Jie (Infect Immun, 2018)
There is established evidence that cytotoxic CD8(+) T cells are important mediators of immunity against the bovine intracellular protozoan parasite Theileria parva. However, the mechanism by which the specific CD8(+) T cells kill parasitized cells is not understood. Although the predominant pathway used by human and murine CD8(+) T cells to kill pathogen-infected cells is granule exocytosis, involving the release of perforin and granzyme B, there is to date a lack of published information on the biological activities of bovine granzyme B. The present study set out to define the functional activities of bovine granzyme B and determine its role in mediating the killing of T. parva-parasitized cells. DNA constructs encoding functional and nonfunctional forms of bovine granzyme B were produced, and the proteins expressed in Cos-7 cells were used to establish an enzymatic assay to detect and quantify the expression of functional granzyme B protein. Using this assay, the levels of killing of different T. parva-specific CD8(+) T cell clones were found to be significantly correlated with the levels of granzyme B protein but not the levels of mRNA transcript expression. Experiments using inhibitors specific for perforin and granzyme B confirmed that CD8(+) T cell killing of parasitized cells is dependent on granule exocytosis and, specifically, granzyme B. Further studies showed that the granzyme B-mediated death of parasitized cells is independent of caspases and that granzyme B activates the proapoptotic molecule Bid.